2020
DOI: 10.1111/bph.14934
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol is a centrally acting analgesic using mechanisms located in the periaqueductal grey

Abstract: Background and Purpose We previously demonstrated that paracetamol has to be metabolised in the brain by fatty acid amide hydrolase enzyme into AM404 (N‐(4‐hydroxyphenyl)‐5Z,8Z,11Z,14Z‐eicosatetraenamide) to activate CB1 receptors and TRPV1 channels, which mediate its analgesic effect. However, the brain mechanisms supporting paracetamol‐induced analgesia remain unknown. Experimental Approach The effects of paracetamol on brain function in Sprague‐Dawley rats were determined by functional MRI. Levels of neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…The fact that neurological dysfunction underlies both sleep and attentional issues in children [ 40 ], suggests that an important mechanism of influence may be the impact of acetaminophen on prenatal neurology, which may impact the regulation of attention and sleep in the preschool period. On this note, acetaminophen has been found to be associated with reduced brain connectivity of the amygdala, a part of the brain responsible for self-regulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that neurological dysfunction underlies both sleep and attentional issues in children [ 40 ], suggests that an important mechanism of influence may be the impact of acetaminophen on prenatal neurology, which may impact the regulation of attention and sleep in the preschool period. On this note, acetaminophen has been found to be associated with reduced brain connectivity of the amygdala, a part of the brain responsible for self-regulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…When patient has needle aversion or needle phobia Despite its prevalence, reported musculoskeletal pain is often under-diagnosed in adolescents [153,154]. Healthcare providers may be unfamiliar or not trained to diagnose chronic pain, muscle trigger points, palpable pain points, and fascia in tension [155][156][157][158]. Presenting symptoms such as neck pain, shoulder pain, abdominal pain and headaches do not immediately direct a physician to look for a myofascial component to pain.…”
Section: Case Based Discussion Of Important Pointsmentioning
confidence: 99%
“…Pain Management -Practices, Novel Therapies and Bioactives receptors, PLC, DAGL and CB1 receptors, associated with the release of glutamate and GABA -through the endocannabinoid systems [155]. Though the molecular mechanisms that provide analgesia are beginning to come to light, there is also potential substantial detrimental side effects of APAPs.…”
Section: Paracetamol (Acetaminophen N-acetyl-p-aminophenol; Apap)mentioning
confidence: 99%
“…This could help to explain why APAP may not have significant clinical effect on conditions such as osteoarthritis (further details below; [153,154]). A recent study confirmed that APAPs act mainly on central analgesic pathways, showing that APAP modifies the activity and connectivity of analgesia via FAAH, activating a signalling cascade involving TRPV1 channels, mGlu5 receptors, PLC, DAGL and CB1 receptors, associated with the release of glutamate and GABA -through the endocannabinoid systems [155]. Though the molecular mechanisms that provide analgesia are beginning to come to light, there is also potential substantial detrimental side effects of APAPs.…”
Section: Paracetamol (Acetaminophen N-acetyl-p-aminophenol; Apap)mentioning
confidence: 96%